Computer Organization - Hamacher Carl.; Vranesic, Zvonko; Zaky, Safeat (Boston : Mc Graw Hill, 2002)
Suitable for a one-semester course in engineering or computer science programs, this text has hardware and software-oriented topics. It uses examples drawn from commercially available computers. The machines discussed include the Motorola 680X0 and 683XX families, Intel 80X86, Pentium families, ARM family, and the Sun Microsystems Sparc family.
Keywords: Computer organization; Ordinateurs -- Conception et construction